Polska socjologia rodziny w zmienionej przestrzeni społecznej minionego XX-lecia = Polish family sociology in the altered social space of the past 20 years - Wachowiak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Today`s scope of research problems (sometimes of social character) conveys issues such as familisation and defamilisation of pro-family policy, faces of Polish poverty and related inclusive strategies, alternative forms of marriage and family, and mixed marriages of different cultural and ethnic origins. The increase in the number of families of mono-parental character as a peculiar indication of progressing de-institutionalisation, desacralisation and detraditionalisation of family is yet another result of transformation, observed by contemporary Polish researchers.
Keywords: rodzina; socjologia rodziny; przestrzeń społeczno-kulturowa